PENGENALAN PENGENALAN MICROSOFT OFFICE DI TK KUSUMMA MULIA SUMBERREJO BADAS KABUPATEN KEDIRI - Imam Saukani; Muhamad Rifai; Guntur Yanuar Astono; Irfin Sandra Asti; Miftakhul Huda; Hari Kurnia Safitri (P3M Politeknik Negeri Malang, 2024)
Integrated Primary Education (TK Kusuma Mulia) is a basic education activity that is organized by, for, and with the assistance of primary education officers. Therefore, TK Kusuma Mulia is a community-driven initiative in the field of basic education, with the village head as the responsible party. A.A. Gde Muninjaya (2002:169) states: